Study of Free/Total Morphine-Ratio in Blood After Heroin Intake as a Tool to Predict the Outcome of Heroin-Intoxication: Study of Free/Total Morphine-Ratio in Blood After Heroin Intake as a Tool to Predict the Outcome of Heroin-Intoxication - I M.A.G. Wirasuta; H.-J. Duchstein; H. Kijewski (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2012)
The time course of free/total morphine ratio (f/t M-ratio) after i.v. heroin administration in both healthy people and patients with liver or renal insufficiency was pharmacokinetically simulated. In the 502 cases of heroin consumption investigated in this study, the morphine blood levels and f/t M-ratio were registered, arranged, and statistically analysed. Total morphine blood levels in survivors and non survivors were 0.010-3.900 µg/ml (with 0-0.275 µg/ml of free morphine) and 0.010-8.570 µg/ml (with 0-2.200 µg/ml of free morphine), respectively. Therefore the respective ranges of f/t M-ratiolevels in survivors and in lethal cases were 0-0.786 and 0-0.935. Based on this simulation, the f/t M-ratio after heroin injection was determined by the time elapsed since the last dose and individual pharmacokinetics of heroin and its metabolites. This ratio is independent to the heroin dose. Keywords: Heroin; Morphine; Lethal intoxication; Pharmacokinetic simulation